Effects of BMI and grip strength on older adults' falls—A longitudinal study based on CHARLS - Lei Huang; Xiaoxin Shen; Yuliang Zou; Yanming Wang (Frontiers in Public Health)
BackgroundBody Mass Index (BMI) and grip strength are potentially important risk factors for falls among the older adults. Currently, there is no consensus on the combined effects of grip strength and BMI on falls in the older adults, particularly among the Chinese older adults.ObjectiveTo investigate the incidence of falls among older adults in China and explore the association between BMI and grip strength and the risk of falls in older adults.MethodsData of participants over 60 in China Health and Retirement Longitudinal Study in 2011 and 2013 were collected. Sociodemographic variables, lifestyle, chronic disease status, history of falls and depression and cognitive status were obtained through the 2011 baseline questionnaire. Height, weight and grip strength were collected from a unified physical examination in 2011. Falls during the follow-up period were obtained through the follow-up questionnaire in 2013. Logistic regression was used to explore the association between BMI and grip strength and the risk of falls.ResultsThree thousand six hundred and eighty-five participants over 60 (67.14 ± 6.08) were included, with a fall incidence rate of 17.37%. The fall incidence rate in females (21.15%) was higher than that in male (13.46%). After adjusting covariates, high grip strength was associated with lower falls risks in general population (OR = 0.76; 95 CI: 0.630–0.923) and males (OR = 0.68; 95 CI: 0.503–0.919). Underweight was associated with lower falls risks in general population (OR = 0.77; 95 CI: 0.595–0.981) and females (OR = 0.69; 95 CI: 0.486–0.962) compared to the normal BMI group. Compared with the low grip strength group, females with high grip strength (OR = 0.54; 95 CI: 0.29–0.98) had a lower risk of falls in the underweight BMI group and males with high grip strength (OR = 0.63; 95 CI: 0.43–0.92) had lower risk of falls in the normal BMI group.ConclusionsHigh grip strength and underweight BMI are independently correlated with a lower fall risk, which varies between males and females.